Tasyahud Perspektif Hadis Nabi (Suatu Kajian Hadis) - Fadhlina Arief Wangsa; Nurul Iqram Asdar (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2023)
Differences in terms of understanding and practice from various groups, not only within the community, but there are also differences among the clergy, especially the scholars of the four schools of thought. This research is a library research, by collecting related literature and then presenting it in a qualitative descriptive manner, namely displaying the data as it is. There are different views regarding the reading, sitting position and position of the fingers at the time of the final tasyahud which is a difference in understanding or interpreting a hadith. However, sitting at the end of the day is a must (rukun) when performing prayers. Sitting last in prayer, some are done with iftirosy or Tawarruk. There are also various tahiat pronunciations contained in the hadith that can be practiced.